2009
DOI: 10.1021/ic900224b
|View full text |Cite
|
Sign up to set email alerts
|

A Cyano-Bridged CrIIICoII Ferromagnet with a Chiral Nanotubular Structure Constituted of Interlocked Single and Double Helices

Abstract: We have synthesized an unprecedented 3D cyano-bridged Cr(III)-Co(II) compound that self-assembles into a periodically ordered, homochiral interlocking structure composed of left-handed single helices and right-handed double-helical strands. It displays four-connected 6(4)8(2) chiral networks and exhibits ferromagnetic order below 12 K. The formation of the helical structure results in the creation of helical tubular channels in the crystal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 30 publications
(27 reference statements)
1
23
0
Order By: Relevance
“…geometry , . Nevertheless, several examples of linear (H 2 dabph) or macrocyclic ligands (15‐pydienN 3 O 2 , 15‐pydienN 5 , 15‐pyN 3 O 2 , tdmmb, or more recent TODA) (Figure S1) provided seven‐coordinate pentagonal bipyramidal complexes with a pentadentate ligand in the equatorial plane, which show a large easy‐axis magnetic anisotropy ( D < 0) in the case of Fe II and Ni II complexes, and on the other side, a large easy‐plane magnetic anisotropy ( D > 0) in the case of Co II complexes. Slow relaxation of magnetization was observed for [Fe(H 2 dabph)Cl 2 ] and [Fe(H 2 dabph‐NH 2 )Cl 2 ] ( τ 0 = 5 × 10 –9 s and U eff = 53 cm –1 ), for [{Ni(H 2 dabph)} 3 {W(CN) 8 } 2 ] (below the blocking temperature T N = 3.6 K, τ 0 = 1.6 × 10 –9 s, U eff = 30 K), and for many different Co II complexes , , , .…”
Section: Introductionmentioning
confidence: 99%
“…geometry , . Nevertheless, several examples of linear (H 2 dabph) or macrocyclic ligands (15‐pydienN 3 O 2 , 15‐pydienN 5 , 15‐pyN 3 O 2 , tdmmb, or more recent TODA) (Figure S1) provided seven‐coordinate pentagonal bipyramidal complexes with a pentadentate ligand in the equatorial plane, which show a large easy‐axis magnetic anisotropy ( D < 0) in the case of Fe II and Ni II complexes, and on the other side, a large easy‐plane magnetic anisotropy ( D > 0) in the case of Co II complexes. Slow relaxation of magnetization was observed for [Fe(H 2 dabph)Cl 2 ] and [Fe(H 2 dabph‐NH 2 )Cl 2 ] ( τ 0 = 5 × 10 –9 s and U eff = 53 cm –1 ), for [{Ni(H 2 dabph)} 3 {W(CN) 8 } 2 ] (below the blocking temperature T N = 3.6 K, τ 0 = 1.6 × 10 –9 s, U eff = 30 K), and for many different Co II complexes , , , .…”
Section: Introductionmentioning
confidence: 99%
“…As a well-known bridging ligand, the cyanide group generally has unique advantages in assembling bimetallic or even trimetallic magnetic CPs, since cyanide-bridged CPs are usually synthesized by a stepwise assembly strategy based on building blocks containing different magnetic carriers (Pardo et al, 2011;Zhang, Xue et al, 2016;Wang, Southerland et al, 2012;Zhang & Sato, 2010;Shatruk et al, 2009). Up to now, in order to clarify the magneto-structural correlation of lowdimensional magnetic systems and to prepare interesting lowdimensional molecule-based magnetic materials, we have developed a series of cyanide building blocks containing larger equatorial plane ligands and two trans-cyanide groups (Zhang et al, 2013;Zhang, Si et al, 2014;Shi, Lan et al, 2018;Shi, Meng et al, 2018;Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…They generate very robust Co II and Mn II complexes with high preference for octahedral coordination and prevent their oxidation to Co III and Mn III , respectively. Moreover, it has been shown that the geometry of these ligands can enhance the local magnetic anisotropy of high [10]. The synthesis of 2 was performed in a glove box operating under argon using degassed solvent by freeze-pump-thaw technique prior to use.…”
Section: Introductionmentioning
confidence: 99%